Вдосконалення методики тестового контролю знань при дистанційному навчанні з послідовним уточненням та корегуванням - Мацулевич, Олександр Євгенович; Мацулевич, Александр Евгеньевич; Matsulevych, Oleksandr; Федоров, В. В. (ТДАТУ, 2021)
UK : У роботі пропонується вдосконалення методики тестового контролю знань студентів з використанням методу послідовного уточнення та способу коригувального контролю знань в умовах дистанційного навчання. EN : The method of test control of knowledge of students is in-process offered with the use of method of successive clarification and method of correcting control of knowledge in the conditions of the controlled from distance teaching.
Іmprovement of methods of test knowledge test control in distance learning with consistent clarifications and adjustments
Keywords: комп'ютерне тестування; тест із послідовним уточненням; дистанційне навчання; тести для корегування; the computer testing; test with successive clarification; controlled from distance teaching; tests for a correction